PENGEMBANGAN INSTRUMEN EVALUASI KOMPETENSI SOFTSKILL MAHASISWA UNTUK MENGUKUR KESIAPAN DIRI MENGHADAPI DUNIA KERJA DI FITK UIN MAULANA MALIK IBRAHIM MALANG - Fitriah, Nurlaeli (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
Competence of softskill both interpersonal and intra-personal competencies are associated with an attitude that is owned by an individual. A person's attitude will affect the acceptance of the individual in a social environment in which the individual resides. Is necessary for students to identify the extent of the environmental acceptability of the students themselves. It will be easier with the ability of students to evaluate and measure regularly softskill its competence through raw instrument developed in this study. The results showed students soft skill competency evaluation instrument to measure the readiness of students in the world of work has to be used as a tool or instrument that is reliable. This is demonstrated through expert validation test and field test. Of expert validation test validates 56 items of 72 items was developed. And the field test 55 items declared valid and reliableKeywords: instrument, self-evaluation